Annual audit of neonatal morbidity in preterm infants. - Cooke, R W (1992)
Annual odds ratios, standardised for known confounding variables, were used to examine trends in major neonatal morbidities among 3220 preterm infants of less than 35 weeks' gestation admitted to a regional referral centre between 1980 and 1991. Despite improved survival, the risk of major cerebral haemorrhage, ventriculoperitoneal shunt insertion, and necrotising enterocolitis was unchanged. A recent reduction in risk of pneumothorax and persistence of the arterial duct was noted. An increased risk for chronic lung disease over time could be accounted for by increased survival, although a similar increase in risk for infection remained unexplained.